Finding Chika : a little girl, an earthquake, and the making of a family - Albom, Mitch, 1958- (Harper, an imprint of HarperCollinsPublishers, 2019)
Chika Jeune was born in Haiti shortly before the devastating 2010 earthquake. When Chika is diagnosed with a life-threatening illness, a doctor tells her orphanage that no doctor in Haiti can help. Mitch Albom and his wife Janine bring Chika to Detroit to see if they can find her help and discover a family they didn't know they were looking for.